(untitled) (Research, Society and Development, 2019)
Third Sector organizations are undergoing several changes in recent years to increase visibility in the marketplace and offer products and services that in fact add value to the beneficiaries. In this context, this study seeks to guide the Sister Helena Child Education Center, a company in the Third Sector, regarding the importance of planning and marketing plan. The method adopted in this study was the exploratory and bibliographical research, using the semistructured interview with the main manager of the institution, as well as informal surveys carried out with the community where the Helena Infant Education Center is inserted. As a result, it was possible to understand the organization and to marketing strategies for the Sister Helena improve its services and add value to the beneficiaries.